Penanaman Konsep Bahan Ajar Era Pandemi Covid-19 di SD Karang Tengah Kota Tangerang - Amanda, Nur Zakia; Hothimah, Ryani Husnul (MASALIQ, 2022)
The concept of teaching materials that are most preferred by students uses methods that are appropriate to the characteristics of students and the social environment so that learning can create strong characters for students and can foster social sensitivity, and also uses language that is easy to understand and good, so that students will not find it difficult to understand the learning itself. Using methods that are varied so that they are easy to understand with the circumstances surrounding the student's own environment. The process of preparing teaching materials goes through the following stages: (a) Preliminary study, by conducting interviews with teachers. Study of syllabus analysis and analyzing basic competencies in the preparation of teaching materials (b) Collecting learning resources and literature as well as the main points of the material to be compiled. (c) Drafting of teaching materials. (d) Limited trial of the product. (e) Data processing and evaluation.